2022
DOI: 10.1002/ehf2.13946
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of B‐type natriuretic peptide in patients with moderate mixed aortic valve disease

Abstract: Aims Data on B‐type natriuretic peptide (BNP) levels and adverse outcomes in patients with moderate mixed aortic valve disease (MAVD), defined as moderate aortic stenosis (AS) and regurgitation (AR), are scarce. Therefore, this study investigated the impact of BNP on the clinical outcomes in such patients. Methods and results Clinical data from 81 patients (mean age, 74.1 ± 6.8 years; 50.6%, men) treated for moderate MAVD and left ventricular ejection fraction (LVEF) ≥ 50% during 2010–2018 were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Another potential would be to apply HF evaluation to moderate VHD to predict the disease progression and optimize intervention timing. The latter is supported by a study of 81 patients with moderate and mixed aortic valve disease, in which age and B‐type natriuretic peptide levels were associated with adverse events 28 …”
Section: Valvular Heart Diseasementioning
confidence: 86%
See 1 more Smart Citation
“…Another potential would be to apply HF evaluation to moderate VHD to predict the disease progression and optimize intervention timing. The latter is supported by a study of 81 patients with moderate and mixed aortic valve disease, in which age and B‐type natriuretic peptide levels were associated with adverse events 28 …”
Section: Valvular Heart Diseasementioning
confidence: 86%
“…The latter is supported by a study of 81 patients with moderate and mixed aortic valve disease, in which age and B-type natriuretic peptide levels were associated with adverse events. 28 In patients with HFrEF, functional mitral regurgitation (MR) is frequently observed and associated with poor prognosis. A recent meta-analysis of edge-to-edge transcatheter mitral repair revealed a lower mortality of patients with functional MR of non-ischaemic compared with ischaemic origin.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“… 12 14 22 23 Recently, Onishi et al demonstrated in a small MAVD population (ie, 81 patients) that BNP levels are independently associated with the endpoint of all-cause mortality, heart-failure hospitalisation and AVR. 24 Nevertheless, as BNP or Nt-proBNP level increase with age and in women, and their elevation is lower in valvular heart diseases than heart failure, the use of the clinical activation ratio (ie, over the maximal expected value for age, sex and assay) has the advantage to take into account interpatient variability. 25 In this study, median absolute Nt-proBNP value and its ratio were higher than what is observed in isolated AS or isolated AR, reflecting the presence of both volume and pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with moderate-to-severe MAVD, high BNP levels were correlated with worse LV-GLS, higher LV-mass index, elevated left atrial volume index, and higher prevalence of moderate or greater tricuspid regurgitation, which are significantly associated with critical clinical outcomes. Previous studies demonstrated worse outcomes in patients with moderate MAVD when compared to those with either moderate AS or AR alone ( 25 ).…”
Section: Introductionmentioning
confidence: 94%